Effects of no-tillage and ploughing on roots of maize and leguminous crops - Maurya, P.R; Lal, R. (1980)
Root development of maize (Zea mays), soyabean (Glycine max), cowpea (Vigna unguiculata), and pigeonpea (Cajanus cajan) was investigated with and without tillage. Observations were made at different growth stages by digging trenches normal to the rows, by core sampling, and by observing growth of roots against glass windows. There were more maize roots in the surface layer (0–10 cm) with no-tillage than in conventionally ploughed plots, but at 10–40 cm maize roots were more abundant and soyabean and pigeonpea roots less so in the no-tillage plots.